The Presidentialization of politics a comparative study of modern democracies - Poguntke, Thomas; Webb, Paul (Paul D.) (Comparative politics., 2005)
Leading experts examine and compare the changing role of political parties and their leadership in 14 modern democracies. It is shown how they are increasingly following a presidential logic of governance, through which leadership is becoming more central and more powerful, but also increasingly dependent on appeal to the mass public.